Effects of Feeding Flaxseeds and Rapeseeds on Milk Fatty Acid Composition in Crossbred Dairy Cattle - Bhavsar, Maitri Y.; Pandya, Paresh R.; Patel, Yogesh G.; Shah, Shailesh V.; Bhavsar, Prakrutik P. (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Effects of feeding oil seeds on fatty acid profile of milk fat was studied on fifteen multiparous HF × Kankrej dairy cows (15 DIM) fed with three experimental diets, viz., T1: control, Total Mixed Ration (TMR) without oil seeds; T2: TMR with ground flaxseeds @ 4.5% and T3: TMR with ground rapeseed @ 4.5%. The experimental TMRs were offered along with 15 kg green cereal fodder as per the guidelines of ICAR standards for 120 days. The milk samples were collected at the end of the experiment for fatty acid analysis. The results revealed significant (p<0.05) increase in the concentration of total unsaturated fatty acids by 21.5 and 29.5% and significant decrease in the saturated fatty acids by 8.0 and 11.0 % in T2 and T3, respectively, as compared to T1. Medium Chain Fatty Acids decreased significantly (p<0.05) in T2 and T3, while Short Chain Fatty Acids remained at par among all treatments. The Long Chain Fatty Acids increased significantly (p<0.05) in T2 and T3 groups, respectively, as compared to T1. The concentration of Omega 3 was found higher by 16.3 and 69.0% in T2 and T3 than T1. The significantly higher Omega 9 fatty acids concentration was found in both T2 and T3 by 32.57 and 30.0%, respectively, as compared to T1. Treatments had no effects on DMI, milk yield and milk composition. It is concluded that feeding flaxseeds and rapeseeds to dairy cows @ 4.5% in TMR altered milk fatty acid composition in beneficial way by increasing healthy fatty acids and decreasing non-desirable fatty acids.